2017
DOI: 10.12944/crnfsj.5.3.04
|View full text |Cite
|
Sign up to set email alerts
|

Improving Nutritive Value of Maize-Ogi as Weaning Food Using Wheat Offal Addition

Abstract: The deficiency in affordable nourishing foods for neonates after weaning has been major concern in developing countries and this has contributed to increased malnutrition rate, illnesses and even children’s mortality rate. The addition of wheat offal to traditionally affordable ‘Ogi’ as an alternative approach for combating the threats of protein malnutrition in neonates was explored in this work. Wheat offal was added at increasing levels of 0, 20, 40, 60, 80 and 100 w/w% as fortifying feed with prepared maiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Oral inoculation solution of Lactobacillus spp. was prepared to contain a final concentration of 1x10 9 lactobacilli/ml and given to the rats for two weeks after which faecal samples from each rat was collected the day of sacrifice and analysed using MRS agar for the enumeration of total faecal LAB count.…”
Section: Probiotic Administration and Total Faecal Lab Countmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral inoculation solution of Lactobacillus spp. was prepared to contain a final concentration of 1x10 9 lactobacilli/ml and given to the rats for two weeks after which faecal samples from each rat was collected the day of sacrifice and analysed using MRS agar for the enumeration of total faecal LAB count.…”
Section: Probiotic Administration and Total Faecal Lab Countmentioning
confidence: 99%
“…7-,9 The addition of other ingredients such as wheat offal to ogi help to further fortify it and reduced malnutrition problems among infants. 9 Kunu-zaki is a popular non-alcoholic Nigerian beverage made from grains. This drink is very common among the Northerners of Nigeria.…”
mentioning
confidence: 99%
“…Sample B showed the highest percentage of protein content and the lowest percentage of carbohydrate content. Protein is known to enhance the formation of antibodies which helps the body fight infections and also, it helps to build, maintain and repair new tissues especially in infants [21].…”
Section: Effect Of Tomato Juice On the Proximate Analysis Of Yoghurtmentioning
confidence: 99%
“…Nugraheni et al, 10 and A. Kanchana et al, 11 used resistant starch type 3 (RS3) andoryza sativa (red rice)flakes to make crackers and snacks that can as a functional food to improve diabetes, obesity and metabolism.Timbadiya et al, 12 replaced with peanut butter to reduce saturated fatty acids in cookies not only had a greater appreciable sensory quality, but also reduce heart disease risk through consumption of beneficial mono and poly unsaturated fats. Ajanaku et al, 13 indicated the maize-Ogi with abundant protein sources would as an alternative approach for combating the threats of protein malnutrition in neonates.Further, Biswas et al, 14 evidenced the hypoglycemic and hypolipidemic efficiency ofvaluable components from watermelon (Citrullus vulgaris) seed kernel sonmale albino rats.…”
Section: Editorialmentioning
confidence: 99%